The Evaluation of Over Current Relay and Ground Fault Relay Settings on Power Transformers - Fatwa Ulhuda, Fikri; Azhari Zakri, Azriyenni; Ali, Umair (International Journal of Electrical, Energy and Power System Engineering, 2024)
Power transformer is an important component of the substation and has an important role in the electric power distribution system. During operation the power transformer can’t be isolated from distribution system when abnormal conditions or faults occur. A fault in the power transformer will have huge impact on the power transformer itself. The substation has an installed capacity of 60 MVA of power transformers, and during operation there is a possibility of relay failure, which may interrupt the power distribution process to the load. To avoid this failure, it is necessary to analyse the settings of Over Current Relay (OCR) and Ground Fault Relay (GFR) on the 60 MVA transformers. The analysis was carried out by simulating short circuit faults of the electrical system in the ETAP software application, and then configure the setting of the relay by referring to the magnitude of the short circuit current value for phase to phase and phase to ground. The results of this analysis are used as a reference to determine the OCR and GFR relay values in the power transformer. The results obtained show that the recommended value for OCR setting on 150 kV power transformers is 0.92 second while for GFR is 0.96 second, and for the 20 KVA power transformers the OCR and GFR setting values are 0.40 and 0.20 seconds respectively. Comparison based on the results of the setup data and the analysis data has carried out, there is difference in the working time of the relay, with a difference of 5%, where the value of the analysis results is not much different from the conditions in the field.